Ship-building and navigation in the Indian Ocean Region, AD 1400-1800 - Mathew, Kuzhippalli Skaria (New Dehli : Munshiram Manoharlal Publishers, 1997)
Collection of contributed articles presented at an international seminar held in February 1995.
Includes bibliographical references and index.
Keywords: Shipbuilding industry -- India -- History; Navigation -- India -- History; Indian Ocean -- Navigation -- History; Merchant marine -- India -- History